Analisis Pengukuran Kinerja Berbasis Balanced Scorecard Pada Rumah Sakit Robert Wolter Mongisidi Manado - Rompas, Merlin Arliany; Karamoy, Herman; Lambey, Linda (Universitas Sam Ratulangi, 2019)
Abstract. This study is purposed to develop the Analysis of balanced scorecard based performance measurement at the Wolter Mongisidi Hospital, Manado. This study consists of empirical surveys based on comprehensive questionnaires, followed by individual and in-depth interviews, as well as the analysis of relevant documents. The data were collected from administrative and healthcare staff located at selected departements in Wolter Mongisidi Hospital. The interview participants were selected from the staff and healthcare personnels who are actively engaged in performance measurement activities. Triangulation was pursued through the multiple sources of evidences. The findings of the study are beneficial in terms of the lessons learned for managerial practices. They provide useful knowledge and understanding of the balanced scorecard based performance measurement in public hospital, particularly Wolter Mongisidi Hospital, Manado. The study contributed to literature in terms of the development of a performance measurement model. The modified performance measurement model is intended to make it easier for the hospital to engage in the performance measurement process, particularly in measuring performance indicators by using the balanced scorecard. The proposed performance measurement model may assist Wolter Mongisidi Hospital to carry out their performance measurement reporting and eventually could provide a positive impact on accreditation status. This study also presents a knowledge base for further research in similar studies and expands the findings in the context of public hospitals in Indonesia.Keywords: Performance measurement, balanced scorecard, financial perspective, customer perspective, internal process perspective, growing and learning perspective.Abstrak. Penelitian ini bertujuan untuk menganalisis pengukuran kinerja berbasis balanced scorecard di Rumah Sakit Wolter Mongisidi, Manado. Penelitian ini terdiri dari survei empiris berdasarkan kuesioner komprehensif, diikuti oleh wawancara individu dan mendalam, serta analisis dokumen yang relevan. Data dikumpulkan dari staf administrasi dan kesehatan yang terletak di beberapa tempat yang dipilih di Wolter Mongisidi Hospital. Para peserta wawancara dipilih dari staf dan petugas kesehatan yang secara aktif terlibat dalam kegiatan pengukuran kinerja. Triangulasi dilakukan melalui berbagai sumber bukti. Temuan penelitian bermanfaat dalam hal pembelajaran untuk praktik manajerial. Studi ini memberikan pengetahuan dan pemahaman yang bermanfaat tentang pengukuran kinerja berdasarkan balanced scorecard di rumah sakit umum, terutama Rumah Sakit Wolter Mongisidi, Manado. Studi ini memiliki titik puncak yakni konsep pengukuran kinerja. Model pengukuran kinerja yang dirancang dimaksudkan untuk memudahkan rumah sakit untuk melakukan pengukuran kinerja, terutama dalam mengukur indikator kinerja dengan menggunakan balanced scorecard. Model pengukuran kinerja yang diusulkan dapat membantu Rumah Sakit Wolter Mongisidi untuk melaksanakan pelaporan pengukuran kinerja mereka dan akhirnya dapat memberikan dampak positif pada status akreditasi. Studi ini juga menyajikan basis pengetahuan untuk penelitian lebih lanjut dalam studi serupa, dan memperluas temuan dalam konteks rumah sakit umum di Indonesia.Kata Kunci: Pengukuran kinerja, balanced scorecard, perspektif keuangan, perspektif pelanggan, perspektif proses internal, perspektif pertumbuhan dan pembelajaran.